Colonic Abnormalities in Manitoban Children with Helicobacter pylori Gastritis - Upama Banik; Camelia Stefanovici; Jennifer Griffin; Wael El-Matary (Gastroenterology Research and Practice)
Objectives. Association between Helicobacter pylori (H. pylori) and colonic pathology is underinvestigated. The aim of this work was to examine the prevalence and nature of colonic changes in children diagnosed with H. pylori gastritis. Methods. A comprehensive retrospective review of the medical records for all Manitoban children (≤17 years) diagnosed with H. pylori gastritis from January 1996 to May 2015 was conducted. Children with H. pylori gastritis who had colonoscopy were identified. Patients’ demographics, indications for colonoscopy, laboratory and endoscopic findings, and colonic histopathological abnormalities were documented. Results. A total of 231 children were found to have H. pylori gastritis. The mean age at diagnosis was 12.3 ± 4.1 years; 108 (46.6%) were girls. Of the 231 patients, 37 (16%) patients were found to have colonoscopy performed. Indications for colonoscopy included bleeding per rectum, significant weight loss, and hypoalbuminemia. Twenty-two (59%) of 37 children who had colonoscopy had significant endoscopic and histopathological findings on colonoscopy including polyposis and colitis. Boys with colonic changes were diagnosed at an earlier age compared to those without (11.5 ± 7.0 versus 15.0 ± 2.0, p<0.049). Conclusions. Our study may suggest a possible association between H. pylori and a subset of colonic changes in children.